In situ single-cell profiling sheds light on IFI27 localisation during SARS-CoV-2 infection - Chin Wee Tan; Jinjin Chen; Ning Liu; Dharmesh D. Bhuva; Tony Blick; James Monkman; Caroline Cooper; Malvika Kharbanda; Kristen Feher; Belinda Phipson; Emily E. Killingbeck; Liuliu Pan; et al. (EBioMedicine, 2024)
Summary: The utilization of single-cell resolved spatial transcriptomics to delineate immune responses during SARS-CoV-2 infection was able to identify M1 macrophages to have elevated expression of IFI27 in areas of infection.